Development of an Inflammatory Bowel Disease Research Registry Derived from Observational Electronic Health Record Data for Comprehensive Clinical Phenotyping - Anderson, Alyce J. M. (Dig Dis Sci, 2016)
BACKGROUND: Inflammatory bowel disease (IBD) is a heterogeneous collection of chronic inflammatory disorders of the digestive tract. Clinical, genetic, and pathological heterogeneity makes it increasingly difficult to translate efficacy studies into real-world practice. Our objective was to develop a comprehensive natural history registry derived from multi-year observational data to facilitate effectiveness and clinical phenotypic research in IBD. METHODS: A longitudinal, consented registry with prospectively collected data was developed at UPMC. All adult IBD patients receiving care at the tertiary care center of UPMC are eligible for enrollment. Detailed data in the electronic health record are accessible for registry research purposes. Data are exported directly from the electronic health record and temporally organized for research. RESULTS: To date, there are over 2565 patients participating in the IBD research registry. All patients have demographic data, clinical disease characteristics, and disease course data including healthcare utilization, laboratory values, health-related questionnaires quantifying disease activity and quality of life, and analytical information on treatment, temporally organized for 6 years (2009–2015). The data have resulted in a detailed definition of clinical phenotypes suitable for association studies with parameters of disease outcomes and treatment response. We have established the infrastructure required to examine the effectiveness of treatment and disease course in the real-world setting of IBD. CONCLUSIONS: The IBD research registry offers a unique opportunity to investigate clinical research questions regarding the natural course of the disease, phenotype association studies, effectiveness of treatment, and quality of care research.